CONVENTIONAL WRITTEN CORRECTIVE FEEDBACK FOR EFL LEARNERS' WRITING SKILL ENHANCEMENT - Dewi, Atika Kumala; Putri, Elsa Desi; Widiati, Utami (International Journal of Educational Best Practices, 2023)
English as a Foreign Language (EFL) learners around the world have access to various tools for their writing skill enhancement. Those tools are commonly accessed with automated written corrective feedback to help them minimize the errors in writing due to its time efficiency. Additionally, the examples of the written corrective feedback used by EFL learners are commonly Grammarly, Hemingway app, and AI grammar checker. However, they fail to address the pointed needs of EFL learners in writing skill enhancement where English is not the native language, such as the practices in non-native developing countries. Due to writing skill enhancement as the aim of this study, the EFL learners' participation is crucial to its efficacy by conventional model, instead of the automated one. To answer this issue, this study presents a Systematic Literature Review (SLR) analysis of conventional written corrective feedback as learning as the appropriate model for EFL learners' writing skill enhancement as the reflective practices in light of the shortcomings for EFL learners' writing skill enhancement in Indonesia. This SLR study demonstrates that the conventional written corrective feedback has the potential to support the Indonesian EFL learners' writing skill enhancement by comparing current practices of the corrective feedback as learning for EFL learners in Indonesia with national practices and international ones dealing with non-native developing countries reported in the literature. The conventional written corrective feedback is expected to be an efficient sustainable model to enhance the EFL learners' writing skill because of its empowering organic form.